2018
DOI: 10.1097/icl.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Measurement Tools and Dimensional Parameters of Pterygium to Investigate its Impact on Refractive Indices and Ocular Aberrations

Abstract: The percentage of pterygium covering the corneal surface seems to be more associated with the pterygium-related visual disturbances than with horizontal and vertical lengths measured by conventional techniques. Moreover, the new computer-assisted image processing technique can accurately and reliably measure the percentage extension of pterygium on cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Several studies have established a relationship between the size of the pterygium and corneal astigmatism 14 , 15 . Mohammad-Salih and Sharif 14 reported that the total area, extension, and width of the pterygium showed a strong correlation with the magnitude of corneal astigmatism measured by keratometry.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established a relationship between the size of the pterygium and corneal astigmatism 14 , 15 . Mohammad-Salih and Sharif 14 reported that the total area, extension, and width of the pterygium showed a strong correlation with the magnitude of corneal astigmatism measured by keratometry.…”
Section: Discussionmentioning
confidence: 99%
“…34 Fourth, it should be noted that the ground truth of referable pterygium was defined based on the presence of pterygium with >2.50 mm extension towards the cornea or with a base width of >5.00 mm, but did not take total area and fleshiness (ie, thickness) 20 of the pterygium into account. However, previous studies have indicated that horizontal extension along with the base width of the pterygium [23][24][25][26] have the greatest influence on corneal astigmatism and ocular aberrations. Thus, the omission of total area and fleshiness from our definition criteria, unlikely had major bearing on our findings.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] In addition, previous study also showed that medium-sized pterygium (defined as extension onto the cornea with length between 2.03.5 mm and vertical length between 5.1 and 7.0 mm) also had higher ocular aberrations compared with small-sized pterygium (with encroachment of <2.00 mm in length or base width <5.00 mm). 25 26 Building on from these previous findings, we further defined referable pterygium in our study, by using more stringent criteria of >2.50 mm encroachment onto the cornea (measured from the limbus) or base width (at limbus) of >5.00 mm. The size of pterygium was measured using the slit lamp's measurement graticule.…”
Section: Definitions Of Pterygium and Referable Pterygiummentioning
confidence: 99%
“…So far, there were only few researches studying the effect of pterygium on back corneal indices and corneal aberrations. [9][10][11] To evaluate the changes in visual function caused by pterygium, ambient illumination levels has to be studied. Low ambient illumination means larger pupil diameter than that in natural-light condition.…”
Section: Introductionmentioning
confidence: 99%